Debates on Intellectual Property Rights - Paula – Angela VIDRAŞCU (Hyperion Economic Journal, 2014)
This paper supports the understanding of the definition of intellectual property rights and strong connection with intangible assets and, on the other hand, provides a brief presentation of the organizations supporting the protection of such rights. The essential aim of this article is represented by the detailed information obtained as a result of research carried out in order to define, identify and study the application of IPR in general and especially in our country. At the end of the paper I mentioned what involves protecting intellectual property rights and brought little concerned how our country is perceived to protect such rights. Most often, intellectual property is defined as a formal document of title, like a lease, which means that the property is a legal concept distinct from real property that are actually good without concrete material form. Constitute a special category of assets being perceived as an original creation, derived from creative ideas; has or may have a commercial value due to its contribution to earnings for its owner. The need for protection of intellectual property rights has emerged because of the changes in the contemporary society. The aim and purpose of which is to protect human intelligence product and, at the same time, ensuring that consumers benefit from the use of the attributes of this product. Always remember that the violation of intellectual property rights, causes injury to major economic, signifying a strong threat to the consumers health and safety.